Academic Performance Programs: New Directions and (Dis)Connections in Academic Reform - O’Bryant, Camille P. (Journal of Intercollegiate Sport, 2012)
The purpose of this paper is to provide a response to Harrison’s (2012) work. The author suggests that the one-size-fits all approach the National Collegiate Athletic Association (NCAA) has adopted when implementing academic reform measures ultimately hurts the athletes the reforms are intended to benefit.